دراسة درجة التوافق الأولي بين الطعم والأصل لبعض أنواع اللوزيات المنتشرة في طرطوس (Latakia University Journal -Biological Sciences Series, 2018)
The research and work was carried out in Syria / Tartous Governorate / Beit Kamouna / (Tartous Agricultural Center) of Tartous Agriculture Directorate located to the south of the city. (2016) The research aims to test the effect of the date on the degree of compatibility of the first between the rootstocks (peaches, almonds - peaches), which are grafted with a local taste (early Nectarine), the rootstocks of the varieties studied at different dates and commensurate with each of the methods of grafting used are as follows: A: tongue grafting: First date: 16/1 Second date: 1/2 Third date: 17/2 B: B-Breclad and T budding: First date: 3/3 Second date: 18/3 Third date: 2/4. The success rates on almond origin and the three dates studied were respectively (85%, 90% , 95%) The highest was the third date where the third date exceeded the second and the second on the first while the results proved that the cultivar (early Nectarine) can be grafted on the roots (peaches, peaches) on the three dates studied and high success rates, respectively for the peach root (90,90) , 90) and on the rootstock of peaches (100,100,100) and the rootstock of peaches outweigh all rootstocks (almonds - peaches) and the three dates studied. تم تنفيذ البحث في بيت كمونة (مركز زراعي طرطوس ) التابع لمديرية زراعة طرطوس  الواقع الى الجنوب من المدينة عام (2016) هدف البحث لدراسة أثر الموعد في درجة التوافق الاولي مابين أصول (الدراق – اللوز – الخوخ) المطعمة بطعم محلي هو (النكتارين المبكر) ,  طعمت الأصول بالأصناف المدروسة بمواعيد مختلفة وبما يتناسب مع كل طريقة من طرق التطعيم المستخدمة وهي كالآتي: A:التطعيم اللساني :الموعد الأول :16-1الموعد الثاني:1-2الموعد الثالث:17-2 B: البرعمة الروسية(B-Breclad) والبرعمة الدرعية  :Tالموعد الأول:3-3 الموعد الثاني:18-3 الموعد الثالث:2-4, اختلفت نسب النجاح على أصل اللوز وبالمواعيد الثلاثة المدروسة؛ إذ جاءت على التوالي (85%,90%,95%) كان أفضلها الموعد الثالث؛ اذ تفوق الموعد الثالث على الثاني و الثاني على الأول في حين أثبتت النتائج أنه يمكن تطعيم الصنف المدروس (نكتارين المبكر) على الأصلين (الخوخ,الدراق) بالمواعيد الثلاثة المدروسة وبنسب نجاح عالية وهي على التوالي بالنسبة للأصل الخوخ(90,90,90) وعلى أصل الدراق (100,100,100) كما أن أصل الدراق تفوق على أصلي (اللوز والخوخ)  وبالمواعيد الثلاثة المدروسة .